2015 ACC/AHA/HRS Guideline for the Management of Adult Patients With Supraventricular Tachycardia: Executive Summary. Issue 14 (5th April 2016) - Page, Richard L.; Joglar, José A.; Caldwell, Mary A.; Calkins, Hugh; Conti, Jamie B.; Deal, Barbara J.; Estes, N.A. Mark; Field, Michael E.; Goldberger, Zachary D.; Hammill, Stephen C.; Indik, Julia H.; Lindsay, Bruce D.; et al.
Abstract : Supplemental Digital Content is available in the text.